Question and Respond Types in Courtroom: A Forensic Linguistics Analysis - Y. Basri Saktyus Lubis; T. Silvana Sinar; Masdiana Lubis (LingPoet: Journal of Linguistics and Literary Research, 2023)
Employing forensic Linguistics, this qualitative study  describes types of question and respond in Providence, Rhode Island court proceedings. Four transcript case from the Traffict court of  Providence, Rhode Island, United State of America were used as corpora in this study. Using Griffith Question Map ( Griffiths, 2006) and Cooperative Principle to approach the sudy. It was found that the are  seven types of question raised by judge Frank Caprio ( Appropriate Closed Yes/No Question, Probing Question, Inappropriate Closed Yes/No question, Open question, opinoin or statement, leading question, and Multiple question) and three types of respond of defendant ( Maxim of Manner, Quality, and Relevance).